2007
DOI: 10.1128/iai.00668-07
|View full text |Cite
|
Sign up to set email alerts
|

Severe Tryptophan Starvation Blocks Onset of Conventional Persistence and Reduces Reactivation of Chlamydia trachomatis

Abstract: The intracellular survival of the bacterial pathogen Chlamydia trachomatis depends on protein synthesis by the microbe soon after internalization. Pharmacologic inhibition of bacterial translation inhibits early trafficking of the parasitophorous vacuole (inclusion) to the microtubule-organizing center (MTOC) and promotes its fusion with lysosomes, which is normally blocked by Chlamydia. Depletion of cellular tryptophan pools by gamma interferon-inducible indoleamine-2,3-dioxygenase (IDO) is believed to be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 38 publications
2
67
0
3
Order By: Relevance
“…Light microscopy and transmission electron microscopy (TEM) were used to examine the inclusions of the Sip mutants and the L2-GFP strain in untreated and IFN-␥-plus-indole-treated HeLa cells to determine if the Sip mutants had a defect in entering persistence. Inclusions of the Sip mutants were significantly (P Ͻ 0.0001) smaller (but were not fragmented in the manner observed in a prior study of severely tryptophan-starved C. trachomatis [46]) than those of L2-GFP following reactivation, despite being similar or larger in size under normal growth conditions ( Fig. 4A and B).…”
Section: Screen For Ifn-␥ Persistence and Reactivation Mutantsmentioning
confidence: 75%
See 1 more Smart Citation
“…Light microscopy and transmission electron microscopy (TEM) were used to examine the inclusions of the Sip mutants and the L2-GFP strain in untreated and IFN-␥-plus-indole-treated HeLa cells to determine if the Sip mutants had a defect in entering persistence. Inclusions of the Sip mutants were significantly (P Ͻ 0.0001) smaller (but were not fragmented in the manner observed in a prior study of severely tryptophan-starved C. trachomatis [46]) than those of L2-GFP following reactivation, despite being similar or larger in size under normal growth conditions ( Fig. 4A and B).…”
Section: Screen For Ifn-␥ Persistence and Reactivation Mutantsmentioning
confidence: 75%
“…It was unclear if the defects in the Sip mutants in the IFN-␥ persistence model were primarily due to tryptophan depletion or were due to other effects of IFN-␥. C. trachomatis also enters persistence in HeLa cells in the absence of IFN-␥ when tryptophan is limiting and can be reactivated later by the addition of tryptophan or indole to the cell culture medium (46). We compared the number of inclusions seen with L2-GFP, the Sip mutants, and the Sip revertants formed under tryptophanreplete conditions at 24 hpi to the number seen under tryptophanfree conditions when we added tryptophan or indole 24 h postinfection and measured inclusions at 48 hpi.…”
Section: Figmentioning
confidence: 99%
“…Tryptophan metabolism is involved in the modulation of several immune responses, ranging from antimicrobial activity by tryptophan starvation (30), protection of allogeneic fetus (31), amelioration of autoimmune diseases (32,33), tumor resistance (34,35), and chronic granulomatous disease (29). Among the tryptophan metabolic pathways, IDO is one of the best-characterized enzymes in terms of immunological effects (36,37), and many experiments were conducted to investigate the functionality of IDO in immune regulation by blocking its enzymatic activity with 1-methyl-tryptophan.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the most successful state of persistence from the pathogen's perspective can be equated not with absolute starvation for Trp but rather with conditions of substantial limitation for Trp. Thus, Leonhardt et al (71) reported that when Trp availability is curtailed to drastically low levels, persistence is largely blocked and reactivation of surviving cells is minimal. Hence, provisioning of Trp at trickle levels could be an all-important feature needed to help sustain persistent cells indefinitely.…”
Section: Role Of Trp In One Mechanism Utilized By the Human Host As Amentioning
confidence: 99%